Ship weight reduction by parametric design of hull scantling. (1st November 2022) - Aguiari, M.; Gaiotti, M.; Rizzo, C.M.
Abstract: In this paper, a semi-automatic design procedure for concept and preliminary phases of hull structural design is described. It allows investigating the design of ship structures, consisting of a series of stiffened panels surrounded by primary members, assembled to form the hull girder. The optimal configuration of the structural lay-out and the best scantling of each structural component (i.e. platings, ordinary stiffeners and primary elements) is provided, accounting for interactions among all structural components as well as integration of primary, secondary and tertiary responses. The proposed method allows the minimization of the overall weight of hull blocks intended as the sum of stiffened panels' weight (shell and stiffeners) plus that of the surrounding primary members. A dedicated application in VBA language (Visual Basic for Applications) has been developed in which scantling checks have been implemented by applying a few rules formulations after a comprehensive analysis of involved variables defining the state of the hull structural system. The proposed scantling design approach is very practical, it follows well-known hull structural design principles and it takes advantage of the nowadays widely available computation means to update the traditional sequence of the scantling checks in a more rational way and to select the optimal lay-out scantling solutions among truly feasible ones. Highlights: A semi-automatic design procedure for preliminary design of the hull structures proposed. Limit states and domain ranges of variables assessed considering robustness, fabrication and operational constraints. A relatively limited number of feasible solutions are identified and scanned to select the lightest one. Method considers interactions among structural components as well as integration of primary, secondary and tertiary responses. Approach is very practical as it follows traditional structural design principles. It takes advantage of automatic computation means though rationally updating the order of scantling checks.